Stosunek konfederacji barskiej do protestantów - Głowacki, Jerzy Józef (Acta Universitatis Lodziensis. Folia Historica, 2013)
The contemporaries of the Confederacy of Bar were convinced that only abolition of a legal provision passed in 1768 under Russian pressure in favour of non-Catholic Christians could allow for lasting peace in the Polish-Lithuanian Commonwealth. At the same time, the Polish political elites thought that legal parity between religions served only to strengthen Russian influence in the country. The Confederates themselves had never declared war on non-Catholics, and even made an attempt to encourage Orthodox to join them – in order to deprive Petersburg of any pretext for interfering in internal affairs of the Commonwealth. Similarly, they did not undertake any action against Protestants (known as “Dissidents”) whom they nonetheless suspected of collaborating with Russia. This was attributable partly to the fact that leaders of the uprising recognised the necessity of gaining European powers’ support, among whom were non-Catholic nations. Ultimately, following the anticipated defeat of Russia, they expected they would return to the pre-1768 modus vivendi concerning religions, and would punish at least the leaders of the Dissident Party in some way. The Confederacy forbade persecution of Protestants, as all citizens, but simultaneously demanded a greater contribution from them than from Catholics. What is more, the mutual mistrust provoked numerous clashes between Confederates and Dissidents (mainly the German-speaking bourgeoisie of Greater Poland and Royal Prussia), who sometimes enlisted the support of Russian troops. Despite the official stance of Confederate authorities, the rank and file displayed occasional dislike of Dissidents, and were inclined to punish them for “betrayal”. Their antipathy was also founded in religion, as most Confederates believed Catholicism to be the superior faith. It should, however, be noted that there were Protestants among the Confederates, and there is no suggestion that they were mistreated by their peers.